Does oilrig activity react to oil price changes? An empirical investigation - Guro Børnes Ringlund; Knut Einar Rosendahl; Terje Skjerpen (Statistics Norway, Research Department, 2004)
In this paper we analyse how oilrig activity in different Non-OPEC regions is affected by the crude oil price. Oilrig activity outside OPEC is an important indicator for production in the near future, and is more sensitive to the oil price than production from existing fields. We estimate relationships between oilrig activity and crude oil prices using Equilibrium Correction Models (ECM) augmented with a stochastic time trend. The results generally show a positive relationship between oilrig activity and the crude oil price, but the strength of the relationship differs across regions. Rig activity in the US seems to react much faster and stronger to oil price changes compared to other regions. In the long-run the price elasticity in the US is above 1.5. Half the effect is observed after six months. In other regions the long-run elasticity is mainly between 0.5 and 1. Overall, it seems to be a clear relationship between the oil industry structure in the region and the reaction to price changes.
Keywords: C22; Q31; Q41; 330; Oilrig Activity; Oil Prices; Equilibrium Correction Model; Stochastic trend